Power and Politics in the Soviet Union - Cooper, Leo. author. aut Link
XI, 160 p.
Keywords: Analyzes the nature of power in the USSR and its evolution since the Bolshevik Revolution. The main thrust of this work, however, is in tracing the fragmentation of power since Gorbachev introduced his reforms and examining the changes in the power structure as a result of perestroika.